The movement potentiation scale and movement therapy – A study of three cases - Williams, Brogan; Horschig, Aaron; Lock, Andrew; Johnson, David (Journal of Musculoskeletal Surgery and Research)
A study of three separate female volunteers was conducted. The movement potentiation scale™ (MPS) was used as a movement evaluation and pain levels were determined using a Visual Analog Scale (VAS) for pain. The six core movement challenges in the MPS evaluation have a combined point value of 26. After the evaluation, every subject underwent a consecutive five-day functional movement training program, which had an emphasis on movement quality, proprioception, balance, coordination, and optimal biomechanics under suitable stimuli. Provocative daily triggers were determined, and participants were educated on movement. Post-intervention data, including the repeated MPS and VAS pain rating findings, were gathered on the day six. Every participant showed a marked improvement in their MPS score and pain. On day one, participant 1, who was awaiting surgery for ongoing severe lower back pain, had a low MPS score of 5/26. On day six, following the intervention, she reported 0/10 discomfort and a 15/26 MPS score. Participant 2 began the trial with a low MPS score of 7/26, chronic shoulder pain, and paresthesia down her left arm. On day six, she reported 0/10 discomfort, no paresthesia, and an improved 14/26 MPS score. Participant 3 had an MPS score of 8/26; the predominant complaint was urinary incontinence. On day six, she showed an improved MPS score of 18/26, with a 10-day follow-up of nil urine incontinence.